(untitled) (Journal of Universal Science Research, 2025)
Politeness theory (PT) emerged within the pragmatic approach in linguistics. According to this theory, individuals employ specific strategies to facilitate effective communication. These strategies help them create an optimal and comfortable communicative environment. The study considers how social norms, power dynamics and cultural values shape the expression and interpretation of polite behavior in discourse.